A meta-analysis on the influence of national culture on innovation capability. (26th May 2009) - Sun, Hongyi
This paper records the study on the influence of national cultures on innovation capability. It is a meta-analysis of previous studies. Innovation capability is measured according to the research by Porter and Stern (2001). The national culture is measured according to the study by Hofstede (1991). Hofstede's (1991) national culture model covers dimensions such as power distance, individualism, masculinity and uncertainty avoidance. Four hypotheses were formulated accordingly to test the relationship between national culture and national innovation capability. It is found out that individualism, power distance and uncertainty avoidance are correlated with national innovation capability. An innovative culture index (ICI) is formulated for benchmarking.